Effects of time-of-day resistance training on muscle strength, hormonal adaptations, and sleep quality during Ramadan fasting - Triki, Raoua; Ben Abderrahman, Abderraouf; Salhi, Iyed; Rhibi, Fatma; Saeidi, Ayoub; Almaqhawi, Abdullah; Hackney, Anthony C.; Laher, Ismail; Granacher, Urs; Zouhal, Hassane (Frontiers in Nutrition, 2024)
Objectives: We investigated the timing of resistance training (RT) during Ramadan fasting (RF) on muscle strength, hormonal adaptations, and sleep quality. Methods: Forty healthy and physically active male Muslims healthy and physically active male Muslims were enrolled in this study. Subjects were randomly allocated into two experimental groups. Group 1 (FAST, n=20) completed an 8-week whole-body RT in the late afternoon (between 16h and 18h) while fasting. Group 2 (FED, n=20) completed the similar RT protocol compared with FAST at night (between 20h and 22h). The following parameters were analyzed at various time-points: 2 weeks before the start of Ramadan fasting (T0), on the 15th day of Ramadan (T1), on the 29th day of Ramadan (T2), and 21 days after the last day of Ramadan fasting (T3). 1-RM tests were conducted for the squats (1-RMSQ), the deadlift (1-RMDL) and the bench press (1-RMBP). Sleep quality was assessed using the full Pittsburgh Sleep Quality Index (PSQI). Blood samples were taken to determine cortisol, testosterone and IGF-1 levels. Additionally, acute hormonal responses were evaluated before, immediately after (AF), and 30 min after a RT session (AF-30 min) at T0, T1, T2 and T3. Results: Post-hoc tests indicated significant 1-RMSQ (p = 0.03; ES=0.13) and 1-RMDL (p = 0.04; ES=0.21) improvements from T0-T2 for FED. Additionally, post-hoc tests indicated significant increases of cortisol levels among FAST at T1 and T2 compared to T0 (p= 0.05; ES= 0.41, p=0.03; ES= 0.34) and a significant increase in cortisol levels in FED at T1 (p= 0.05; ES=0.29) and T2 (p=0.04; ES=0.25). Post-hoc tests also indicated significant increases of testosterone only among FED at T2 (p=0.04; ES=0.31). Of note, the testosterone levels were significantly higher at T3 compared to T0 (p = 0.05; ES = 0.28) and T1 (p = 0.03; ES = 0.25). No significant group × time interactions were identified for sleep quality (p = 0.07; ES= 0.43). Conclusion: Muslims can safely practice RT during RF. However, training in a fed state during Ramadan might be more effective than during fasted state for the enhancement of maximal strength with better hormonal responses observed.